Composite Steel Joists - Samuelson, David (Engineering Journal, 2002)
Composite steel construction has been recognized for a number of years as one of the most economical systems for constructing building floors. Three options have evolved over the years to meet the requirements for building height limitations and the need to run complex heating, ventilating, electrical, and communication systems: (1) Composite wide flange beams with web openings; (2) Stub girders; and (3) Open web steel joists and joist girders. This paper focuses on the advantages associated with composite open web steel joists, development and testing of open web steel joists, behavior of welded shear studs observed while testing composite joists, case histories of projects using composite joists, unique vibration considerations associated with joist floors, and current status of composite joist specification development.